PERANCANGAN WEBSITE SEKOLAH SEBAGAI MEDIA INFORMASI: STUDI KASUS SDN 168 PEKANBARU : SCHOOL WEBSITE DESIGN AS MEDIA INFORMATION: CASE STUDY OF SDN 168 PEKANBARU - Nuraini, Dwi Nur Indah Sari; Marpaung, Noveri Lysbetti (PADIMAS, 2024)
SDN 168 Pekanbaru is a state elementary school located on Gg. Lestari, Labuh Baru Bar., Kec. Payung Sekaki, Pekanbaru City, Riau, faces problems in conveying information to students and parents, as an educational institution requires effective information media to support communication between schools, students and parents. The aim of this activity is to design and develop a new website that provides comprehensive information about schools that is easy to access. This activity involves writers who act as website developers using web design methods, involving 4 types of users, namely School Principals, Class Teachers, School TU Administrators and Website Administrators. The result of this activity is a website that includes School Profile, Facilities, Vision and Mission, Educator Staff, Gallery and News, which is proven to improve user experience and facilitate access to information for the entire school community. In conclusion, the development of this website succeeded in increasing the efficiency of communication and school operations and provided significant benefits for the entire SDN 168 Pekanbaru community.